New fatty acid and acyl glycoside from the aerial parts of Phyllanthus fraternus Webster - Abuzer Ali; Mohammad Jameel; Mohammed Ali (Wolters Kluwer Medknow Publications, 2016)
Background: Phyllanthus fraternus Webster (Euphorbiaceae) is used to treat dyspepsia, indigestion, jaundice, dysentery, diabetes, influenza, kidney stones, urinary tract diseases, vaginitis, and skin eruptions in traditional systems of medicine. Materials and Methods: The methanol extract of aerial parts of P. fraternus was obtained by soxhlation method. Isolation of compounds was done by silica gel column chromatography. Analytical thin layer chromatography was used to check the homogeneity of eluted fractions. The structures of isolated compounds were established on the basis of spectral studies and chemical reactions. Results: Phytochemical investigation of a methanolic extract of the aerial parts yielded a new fatty acid characterized as cis-n-octacos-17-enoic acid (5) and a new acyl tetraglycoside formulated as n-dodecanoyl-O-β-D-glucopyranosyl-(2"→1‴)-O-β-D-glucopyranosyl-(2"→1‴)-O-β-D-glucopyranosyl-(2‴→1"")-O-β-D-glucopyranoside (7) along with known compounds 1-pentacosanol (1), β-sitosteryl oleate (2), β-sitosteryl linoleate (3), stigmasterol (4) and palmityl glucuronoside (6).